The effect of chronic khat chewing on liver enzyme levels ( a Yemenian study) - Iman Ramzy; Mohammad Abdelbary; Hanan Abdelhafez; Dalia Omran; Mansour Al-Amrany; Aqeel M. Al-Shami (SpringerOpen, 2013)
Background Khat is a natural stimulant from the Catha edulis plant, which grows mainly in Yemen. The liver has been suspected to be vulnerable to the harmful effects of khat use. AimThe aim of the study was to investigate the effect of khat chewing on the liver function in healthy Yemeni individuals. MethodsLiver function tests were performed on 30 chronic khat chewers (group I) and 20 individuals who did not chew khat (group II). Results Twenty percent of group I and only 5% of group II reported abnormally elevated alanine transaminase (ALT) levels, with no statistically significant difference between the mean ALT values (P=0.208); 13.3% of group I showed elevated aspartate aminotransferase levels (P=0.058). With regard to other liver function tests there was no statistically significant difference between the two groups. ALT levels increased with increasing duration of khat chewing. Conclusion Chronic khat chewing causes subclinical hepatocellular damage, whereas transient khat chewing has no effect on the liver function.